Neonatal Screening for Medium-Chain Acyl-CoA Dehydrogenase Deficiency-Alternative Approaches - Rodney J. Pollitt (MDPI AG, 2016)
The challenges inherent in many newborn screening programmes for medium-chain acyl-CoA dehydrogenase deficiency could be overcome by better use of the available second-line tests. Application of "next generation" technologies could minimize many of the problems generated by the current approach to genetic analysis. (Comment on Maier EM. Int. J. Neonatal Screen. 2015, 1, 79-88)